Perilaku Spasio Temporal Tikus Sawah (Rattus argentiventer) Betina - Susilo Hadi; Jusup Subagja; Sudarmaji Sudarmaji (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
This research aimed to study spatio temporal behavior of the female ricefield rat, Rattus argentiventer, including home range, range spans, habitat use and daily activity. Twelve rats were released in two locations of a ricefield area from June 11th until July 24th, 2001. The movement of each rat was monitored using radio-tracking three times a day. The result was used for calculating home range size, range spans, habitat used and daily activities of female field-rats, using the computer program Ranges V. The results showed that the average female ricefield-rat’s home ranges and range spans were 0.84  0.16 Ha and 184.54  22.7m respectively. During daylight, the rats spent 82%, 16% and 2% of their activity living in dikes, in villages and in ricefield respectively. On the contrary, during the night 95%, 3% and 2% of the rats were active in the ricefield, villages and dikes respectively.